Outdoor Recreation Development in Forest Land - Tutut Sunarminto (Media Konservasi, 1996)
One of the many forest benefits, that is very potential to be developed is nature recreation service, due to the increase tendency of nature recreation demand. However, due to the difficulties to clearly see the economical benefits of tourism and recreation activities in forested land especially conservation areas, have caused few investors who are willing to involve themselves in the field of nature recreation service. According to various research, there is a great consumer surplus in outdoor recreation activities and results show increase number of visitors in a conservation areas from year to year.